Atividade antibacteriana de Anacardium occidentale frente a bactérias do grupo eskape - SANTOS, Pâmela Gomes (2024)
The bioprospection of natural products, with antimicrobial action and therapeutic purpose, has been gaining much prominence worldwide, especially considering the high number of microorganisms resistant to conventional treatments. In this context, products derived from Anacardium occidentale, a species native to Brazil and known as the cashew tree, emerge as a promising alternative due to their antimicrobial potential. The present study evaluated the effect of ethanolic extract of A. occidentale (EAO) flowers in vitro, considering the action on the adhesion and biofilm formation of ESKAPE’s bacteria group, as well as on lethal Staphylococcus aureus infection induced in Tenebrio molitor larvae. HPLC and LC- MS determined the chemical composition of the extract. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) determined the antibacterial activity on standard strains of Staphylococcus aureus (ATCC 25923) and Enterococcus faecalis (ATCC 29212), Escherichia coli (ATCC 29922), Klebsiella pneumoniae (ATCC 700603) and in multidrug-resistant clinical strains of S. aureus (MRSA 240016969961 and MRSA 240016969962). The effects of EAO were also evaluated on the viability and biomass of adhesion and preformed and formed biofilms. For the in vivo assays, T. molitor larvae were used to determine the toxicity of EAO, standardize the lethal inoculum of S. aureus, and evaluate the EAO effect after lethal infection with S. aureus. The animals were divided into six groups (N=10) to determine their survival during the lethal infection. Sham: without infection or treatment, and five groups lethally infected with S. aureus (105 CFU/μL), intracelomic and treated with EAO or CIPRO by the same route. Groups EAO1/2: treated EAO in a concentration corresponding to 1/2 MIC (3.12 mg/mL), EAOCIM: EAO in MIC concentration (6.25 mg/mL) and EAO2: treated with EAO corresponding to 2x MIC concentration (12.5 mg/mL). Negative control: received phosphate-balanced salt solution (PBS), CiPro: treated with ciprofloxacin (1,56 μg/mL), The major compounds identified were: shikimic acid, gallic acid, quercetin, isoquercetin, galloyl glucose, digaloyglucose, isomer 1 and isomer 2 of tetragalloylglucose. The MIC values ranged from 6.25 to 50 mg/mL for the strains, with the best activity for S. aureus (MIC=6.25 mg/mL) and the MRSA strains (MIC 12.5 mg/mL). The EAO had bactericidal action according to CBM/CIM. The extract reduced the biomass and viability of adhesion- preformed and formed biofilms of S. aureus. EAO showed low toxicity to T. molitor. Treatment with EAO increased the larvae's survival after lethal infection with S. aureus in a dose-dependent way. In conclusion, EAO prolonged the survival of larvae lethally infected by S. aureus, possibly due to its antibacterial action and its effects on adhesion and biofilms.